An alternative class of ratio-regression-type estimator under two-phase sampling scheme - Isah Muhammad; Yahaya Zakari; Ahmed Audu (CBN Journal of Applied Statistics, 2021)
In this study, a new exponential ratio-regression estimator is developed using an aux- iliary variable for estimating the finite population mean under a two-phase sampling system. The Bias and Mean Square Error (MSE) of the proposed estimator are de- rived and compared with some of the estimators in extant literature. Thus, the condi- tions under which the proposed estimator is better than some existing estimators are provided. Empirically, using four real datasets and simulation study, the proposed estimator performs better than the classical ratio, classical regression, exponential ratio, and exponential regression cum ratio estimator when compared using the cri- teria of bias, mean square error and percentage relative efficiency. The proposed es- timator can be used to estimate the averages of economic variables such as inflation, exchange rate, and standard of living for policy formulation
Keywords: C13; C15; C81; C82; 330; Auxiliary variable; bias; double-sampling; efficiency; mean square error